2000
DOI: 10.1080/00332747.2000.11024895
|View full text |Cite
|
Sign up to set email alerts
|

Higher Brain Blood Flow at Amygdala and Lower Frontal Cortex Blood Flow in PTSD Patients with Comorbid Cocaine and Alcohol Abuse Compared with Normals

Abstract: Posttraumatic stress disorder (PTSD) patients with histories of cocaine and alcohol abuse (CA-PTSD) were compared with normal volunteers. Positron emission tomography (PET) scans with 15O-butanol were used to compare regional cerebral blood flow (rCBF) between the groups during rest and during an auditory continuous performance task (ACPT). CA-PTSD patients had significantly higher rCBF in right amygdala and left parahippocampal gyrus than normals during the ACPT. Normals had higher rCBF at frontal cortex duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(104 citation statements)
references
References 0 publications
7
91
0
6
Order By: Relevance
“…This study provides evidence of a volume reduction of ACC in patients with PTSD. The findings of the present study are consistent with several neuroimaging studies that have suggested dysfunction or neuronal loss in ACC in patients with PTSD (16,17,(42)(43)(44)(45)(46). The results of the present and previous studies support a neuroanatomic model of PTSD that posits a failure of ACC to inhibit a hyperresponsive amygdala (16,43,47,48).…”
Section: Discussionsupporting
confidence: 82%
“…This study provides evidence of a volume reduction of ACC in patients with PTSD. The findings of the present study are consistent with several neuroimaging studies that have suggested dysfunction or neuronal loss in ACC in patients with PTSD (16,17,(42)(43)(44)(45)(46). The results of the present and previous studies support a neuroanatomic model of PTSD that posits a failure of ACC to inhibit a hyperresponsive amygdala (16,43,47,48).…”
Section: Discussionsupporting
confidence: 82%
“…Functional neuroimaging findings using positron emission topography (PET) and functional magnetic resonance imaging (fMRI) suggest that individuals with PTSD exhibit hyperresponsive amygdala activity to trauma or fear-related stimuli (for review, see Shin and Liberzon, 2010), during emotionally neutral tasks (Bryant et al, 2005;Shin et al, 2004b), and even at rest (Chung et al, 2006;Semple et al, 2000). A hyperresponsive amygdala contributes to the exaggerated fear response characteristic of PTSD (Anderson et al, 2003).…”
Section: Clinicalmentioning
confidence: 99%
“…Previous findings for the amygdala are discordant. Most studies report greater amygdalar activation associated with PTSD (Shin et al, 1997;Rauch et al, 2000;Semple et al, 2000;Hendler et al, 2003;Shin et al, 2004;Shin et al, 2005;Williams et al, 2006), but there are contradictory reports of greater activation in controls (Britton et al, 2005;Phan et al, 2006), and numerous studies lack amygdalar findings entirely (Bremner et al, 1999a;Bremner et al, 1999b;Lanius et al, 2001;Shin et al, 2001;Lanius et al, 2002;Lanius et al, 2003b;Sakamoto et al, 2005). Quantitative analysis of signal-to-noise in this region showed poor signal quality using our standard echoplanar imaging sequence at 3T.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A subsequent study confirmed lower ACC activation in the PTSD group for the emotional Stroop condition, and lower activation in inferior parietal lobule, visual association cortex, and precuneus for the classic Stroop condition (Bremner et al, 2004). An auditory continuous performance task study of patients with comorbid cocaine and alcohol abuse also found lower activity in rostral ACC (Semple et al, 2000). Converging support across symptom provocation studies combined with neuropsychological assessment, posit an inability of the PFC to inhibit a hyperresponsive limbic system in PTSD (Bremner et al, 1999b;Rauch et al, 2000;Shin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%